SPATIAL DEVELOPMENT STRATEGY OF RUSSIA: UPDATE VECTORS - Druzhinin, Александр Георгиевич; Kuznetsova, Ольга Владимировна (Geographical Bulletin, 2024)
The large-scale geopolitical and geo-economic changes inherent in the modern world order, complemented by prolonged economic, technological, and demographic trends, are projected onto the Russian space, correcting both its external contour and internal architecture. In this context, the discourse on targets, directions, and ways of activating the territorial socio-economic dynamics of the Russian Federation has revived, and the development of an updated strategy for its spatial development has been reinvigorated. Based on the tools of socio-geographical analysis, the study aims to identify the most important problem areas characteristic of modern Russia, dilemmas, alternatives, and priorities in the field of its spatial development, as well as to substantiate on this basis a conceptual approach to updating the key provisions of the current Spatial Development Strategy of the Russian Federation for the Period up to 2025. The paper notes the internal inconsistency of this document (the prevalence of orientation toward ‘alignment’ within the agglocentric model, the desire to combine centripetal trends with the search for formats to counteract the ‘compression’ of the developed space, etc.) and its simultaneous transitivity, susceptibility to innovation (‘municipalization’ of approaches, consideration of the ‘geopolitics factor’, etc.). The paper emphasizes the need to modify the Strategy by focusing on the exogenous determinants of Russia's spatial development (including the formation of ‘Greater Eurasia’), as well as its scientific, technological, and defense-industrial factors. We substantiate the reasonableness of a more consistent shift in emphasis to the stimulation of interregional and inter-municipal integration, to mutually supportive co-development of regions and municipalities within a single market, transport, logistics, and information space based on the balance of ‘Moscow-centrism’ with the development of other growth poles, expansion, and ‘interlayering’ of their spheres of influence.